Dimensiones epistémicas y cognitivas en la enseñanza de las disciplinas proyectuales. (ARQUISUR Revista, 2010)
This paper presents the relationship between design education and most relevant epistemological paradigms of the discipline and design thinking. The relevance of cognitive theories of learning is derived to the development of pedagogical framework whit rational basis. The cognitive approaches in design are presented and discussed, and a hypothesis is proposed of the importance of explicit acquisition of a representational knowledge in design processes, and in the pedagogical management model, to improve the classical method of tacit learning in the field of design.
Keywords: cognition; knowledge; learning; representation